Keberagamaan Masyarakat Muslim Inklusif di Perum Royal Residence Surabaya: Analisis Fenomenologi Edmund Husserl - Paramaramya Moktikanana Marjuwwa; Isa Anshori (Al Hikmah, 2023)
Abstract: Indonesia is a plural country with many cultures, races, languages and religions. Surabaya is one of big cities in which there is a lot of multicultural interaction. Surabaya people are a society that is tolerant of differences. In Perum Royal Residence, the people adhere to six different beliefs, Islam, Christian, Catholic, Buddha, Hindu and Kong Hu Cu. Muslims as majority community play important roles in forming harmonious relationship among them. This research focus on the relations between Muslims and Christians, Catholics, Hindus, Buddhists and Kong Hu Cu in the application of Inclusivism based on Islamic values. This study was conducted with qualitative methods with interview and observation to collect data. Analysis methods of this study uses Phenomenology of Edmund Husserl which consist of three reductions, phenomenological, eideitic and transcendental. The conclusion of this research is Muslims in Perum Royal Residence apply inclusivism well in their relations with non-Muslims.Keywords: Inclusivism, Islam, Edmund Husserl